Kualitas Papan Partikel Batang Pisang Barangan Berdasarkan Variasi Kadar Perekat Phenol Formaldehida - Johanna Christina Malau; Tito Sucipto; Apri Heri Iswanto (Program studi Kehutanan USU, 2016)
Banana stem is one of alternative materials for particleboard manufacturing. Utilization of banana stems for particleboard can reduce the wood demand for industrial particleboard. The objective of this research was to evaluate the effect of resin level PF to physical and mechanical properties particleboard made from banana stems and to determine of the optimum resin level from particleboard. Varied concentration of PF resin as binder consist of 8%, 10%, 12%, 14%, and 16%. Size thickness and density target of particleboard were 25 x 25 cm2 x 1 cm and 0,70 gr/cm3 respectively. The result showed that, over all for physical properties density and moisture content had fulfill JIS A 5908 (2003). Banana stem particleboards had low dimensional stability. Trend of water absorption and thickness swelling showed that the increasing of resin level resulted of decreasing water absorption and thickness swelling parameter. For mechanical properties, MOE and IB for resin level 16% had fulfill standard. In generally, the high resin level caused improvement mechanical properties of particleboard.Keywords: banana stems, phenol formaldehyde, mechanical and physical properties, particleboard